Change Management in Educational Institutions: Problems, Causes and Alternative Solutions - Hifza Hifza; Susilawati Susilawati; Nuraini Nuraini; Suriadi Suriadi (Al-Hayat: Journal of Islamic Education, 2020)
The purpose of this study is to describe the problems of change management in educational institutions and alternative solutions that can be attempted to overcome these problems. The results showed that the issues that often arise in the process of change in educational institutions are resistance (resistance) to change and the occurrence of momentary switches (temporal variation). Several factors that caused the failure of the change process were: 1) the difference was not well planned; 2) ignoring the human element in managing change; 3) failure to build strong coalitions to drive change; 4) lack of socialization to private educational institutions; and 5) lack of innovation and not empowering the energy to continue evolution. Alternative solutions are: 1) overcoming resistance to change; 2) innovating; and 3) maximizing the power of change in educational institutions, including support for human resources, maximum supervision and support from technology and information systems.